Project for Strengthening the Student Profile of Pancasila Centered on Students at Semen Tonasa II Kindergarten - Ashar Ashar; Sadaruddin Sadaruddin; Reski Idamayanti (PT ARRUS Intelektual Indonesia, 2024)
The project to strengthen the profile of Pancasila students is focused on students in facing the challenges of an ever-evolving era. The importance of character formation and Pancasila values at an early age is the main focus of this project. A holistic and participatory approach method is used to strengthen the understanding and implementation of Pancasila values in children's daily lives. An innovative project implemented in the Kindergarten (TK) environment with the main theme